Rancang Bangun Kontruksi TEG (Thermoelectric Generator) pada Knalpot Sepeda Motor untuk Pembangkitan Listrik Mandiri - S Sugiyanto; Muh Tarum N Umam (Forum Teknik, 2015)
The utilization of waste heat from exhaust gas in motorcycle is a typical application of electricity generation using thermoelectric generator (TEG) technology. The construction of TEG that mounted at outer surface of motorcycle exhaust pipe will depend on quality of threemain components: the support structure, the thermoelectric module, and the heat dissipation system. The components will influence heat conversion to electricity so those are must be well designed to required heat transfer process from the surface of exhaust pipe to hot side and cold side of TEG.     The methods that used are designing good construction of TEG with Aluminum material that will to be installed properly on surface of motorcycle exhaust pipe without disturbing theheat transfer from the surface to the both side of TEG. This design allows the TEG can be assembled easily without damaging the TEG module itself too. Then before testing onmotorcycle, the construction design run testing by the heat transfer software to observe how much heat that generate from the surface and transferred to the both side of the TEG. TEG module used is the HZ-14 which has dimensions of 6.25 cm x 6.25 cm and the selected motorcycle is a 150 cc motorcycle sport type.     The result of TEG construction consists of two main parts, the holder of TEG modules for HZ -14 and a heat sink that adapted to the shape of exhaust pipe motorcycle. The heat sink is also related to the cold sink is made from aluminum fins placed on the cold side of the TEG. The test results generated electrical voltage output indicates that the voltage will begin to be raised shortly after the motorcycle is turned on ,that is about 10 seconds shortly after the motorcycle turned on the voltage generated is 11 mV at idle engine speed range from 1800 to 2000 rpm. The voltage will show stability at 664-665 mV after 15 minutes the motorcycle turned on at engine speed of 4500 rpm . Keywords: heat sinks, motorcycle exhaust pipe, energy conversion, thermoelectric generators,power generation